Geo-engineering characterization of mining material: A case study in Yogyakarta, Indonesia - Budianta, Wawan; Warmada, I Wayan; Hideki, Ohta; Takemura, Jiro (Brawijaya University, 2025)
The extraction and processing of aggregates in quarrying operations leads to environmental degradation through various engineering methods. This study investigated the geo-engineering properties of tertiary volcanic rocks mined from various sites in Sleman and Bantul District, Yogyakarta Province. A total of twelve rock samples were obtained from the study area. This study conducted mineralogical and geotechnical engineering investigations, including microscopic analysis, unconfined compressive strength (UCS) tests, abrasiveness tests (CAI), and rock abrasivity index (RAI) calculations. Mineralogical observation using polarisation microscopy indicated that the rock samples consist of quartz, plagioclase, lithic fragments, and volcanic glass. The UCS test showed varying rock strengths due to resistant minerals in the samples. Similarly, the CAI values varied and were influenced by the quartz mineral content, which is representative of resistant minerals. The Rock Abrasivity Index (RAI) calculation classified the samples as less abrasive, and this characteristic is also affected by quartz content. A significant correlation was observed between the quartz mineral content and the UCS, CAI, and RAI values. This relationship suggests that the quartz mineral content substantially affects the UCS, CAI, and RAI values of the rock samples in the study area. The findings of this study can be used to enhance mining practices and minimize their ecological impact.